Preliminary Phyto-pharmacological Investigation of Duabanga Grandiflora (Roxb. ex DC.) Walpers - Sharmin, Sanjida; Sifat, Tahmina; Azad, Afrina; Reza, ASM Ali; Islam, Mohammad Kaisarul; Sayeed, Mohammed Abu (Bangladesh Pharmaceutical Journal, 2020)
The methanolic extract of Duabanga grandiflora (Roxb. ex DC.) Walpers leaves was investigated to explore in-vitro anti-arthritic, thrombolytic and antioxidant potential and subsequent detection of preliminary phytochemicals. It is used for treating various diseases by folk practitioners and rural people. Initially, BSA protein denaturation method was employed to evaluate in-vitro anti-arthritic potency, where the extract exhibited potent anti-arthritic activity with 73.52±1.01% inhibition of BSA denaturation at a dose of 1000 μg/ml compared to the standard dichlofenac sodium (83.66±1.03% inhibition at 1000 μg/ml dose). In-vitro thrombolytic efficacy was determined using streptokinase (positive control) and water (negative control), and the average lysis of blood clot was found to be 31.12±1.09%, which is indicative towards the thrombolytic effect of the extract. Antioxidant activity was evaluated by the DPPH radical scavenging method followed by the total phenolic and flavonoid content determination. The crude methanolic extract revealed the IC50 value of 129.31μg/ml and 204.89μg/ml against DPPH and standard ascorbic acid, respectively. The total phenolic content and total flavonoid content of the plant leaves were observed to be 52.81±1.74μg/ml and 25.77±1.01μg/ml, respectively. The results indicate that the leaves of D. grandiflora possess favorable anti-arthritic activity, moderate thrombolytic and excellent antioxidant activity, which is demonstrating the presence of alkaloids, phenols, flavonoids and many other biologically important phyto-constituents that needs further exploration. Bangladesh Pharmaceutical Journal 23(1): 54-60, 2020